CMOS variable-gain phase shifter based on time-varying vector-sum method and its application to Ku-band phased array. (January 2023) - Cheng, Guoxiao; Zhang, Jin-Dong; Chen, Qiaoyu; Sima, Boyu; Wu, Wen
Abstract: In this paper, a new time-varying vector-sum method is proposed for variable-gain phase shifter design. By introducing a time variable into the conventional vector-sum phase shifter (VSPS) architecture, high-resolution phase shifting and wide amplitude control can be achieved simultaneously. The proposed time-varying phase shifter (TVPS) is fabricated in 0.13-μm CMOS technology with a core area of 1.76 mm 2 . A ﬁeld-programmable gate array (FPGA) is utilized to generate gain-control timing sequences for phase shifting and on-off timing sequence for amplitude control, which are optimized to achieve a measured sideband suppression ratio of −17.2 dBc. For bidirectional operation, measured results present that the proposed TVPS can achieve a phase resolution of 10-bits, RMS (root mean square) phase error of 0.2–0.5°, RMS gain error of less than 0.2 dB, and gain tuning range of 10.1 dB in the frequency band of 12–18 GHz. The proposed TVPS is applied to a 4-element phased array, and the measured radiation patterns of scanned beams are presented.